ANALISIS EFEKTIVITAS PENGELOLAAN ANGGARAN PENDAPATAN DAN BELANJA DESA (APBDES) PADA DESA MENTARAS, KABUPATEN GRESIK - Wiwin Siswanti; Mochammad Ilyas Junjunan (Politeknik Negeri Malang, 2026)
This study aims to analyze how effective the management of APBDes in Mentaras Village, Dukun District, Gresik Regency in 2024 by consider the principles of transparency, accountability, participation, and budget discipline. This research uses descriptive quantitative method with primary data through interviews with the Finance Staff and secondary data in the form of APBDes and budget realization reports. Data collection was carried out through interviews, documentation, and observation while the effectiveness analysis is based on the ratio referring to the Decree of the Minister of Home Affairs Number 690.900.327 of 1996. The results of this study indicate that the effectiveness of village revenue reached 90.09% and the effectiveness of village expenditure was 91.85%, which is considered effective. However, the revenue sharing from regional taxes and levies only reached 57.74%, thus being declared ineffective due to delays in fund disbursement and a mismatch between targets and actual revenues.